2020
DOI: 10.1002/bse.2641
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy and the policy: A framework for improving the corporate environmental management in supply chains

Abstract: The transition to the circular economy (CE) creates value through the closed‐loop systems, reverse logistics, product life cycle management, and clean production in terms of corporate environmental management. During this transition process, the organization faces many barriers such as financial, organizational, technology‐based, social, policy‐related, market‐based, and logistics‐based barriers. The objectives of this study are to propose a framework highlighting policy‐related barriers for a supply chain in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(121 citation statements)
references
References 95 publications
2
107
0
12
Order By: Relevance
“…Despite the concerns about humanity's impact on Earth and Earth's resources, and the support for CE as expressed in business and political circles [8], the progress of transitioning to a CE is reported to be limited [18,19,29,[62][63][64][65][66]. Several studies, for example [17,18,20,22,26,28,29,64,[67][68][69], report barriers or challenges that businesses experience in their transition towards circularity. For example, Preston [18] identified the following: high up-front costs; complex international supply chains; resource-intensive infrastructure lock-in; failures in company cooperation; lack of consumer enthusiasm; and limited dissemination of innovation, across both emerging economies and developed countries.…”
Section: Barriers For the Transition To Circularitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the concerns about humanity's impact on Earth and Earth's resources, and the support for CE as expressed in business and political circles [8], the progress of transitioning to a CE is reported to be limited [18,19,29,[62][63][64][65][66]. Several studies, for example [17,18,20,22,26,28,29,64,[67][68][69], report barriers or challenges that businesses experience in their transition towards circularity. For example, Preston [18] identified the following: high up-front costs; complex international supply chains; resource-intensive infrastructure lock-in; failures in company cooperation; lack of consumer enthusiasm; and limited dissemination of innovation, across both emerging economies and developed countries.…”
Section: Barriers For the Transition To Circularitymentioning
confidence: 99%
“…De Jesus and Mendonça [29] recognized these technical, market related, and economic barriers, and added 'softer' criteria, such as regulatory, social, and cultural barriers. Kazancoglu et al [68] added that "governmental policies, regulations, and legislations play important role" in the transition towards CE. In one of the most recent studies, Ormazabal et al [22] summarized the barriers found in earlier studies as: lack of financial support, inadequate information management systems, lack of proper technology, lack of technical resources, lack of financial resources, lack of consumer interest in the environment, lack of support from public institutions, lack of qualified professionals in environmental management, and lack of commitment on the part of the organizations' leaders.…”
Section: Barriers For the Transition To Circularitymentioning
confidence: 99%
“…In addition, in a few articles the "Tools, models, framework, methods for decision-making" was combined with other research types. A few examples include with "Business model and management" in an article assessing the costs of municipal waste recycling [96]; with "Economic Model," in an evaluation of the electrical and electronic equipment industry [81]; and with "Policy," in a study developing CE frameworks for the building sector [97] and the Supply Chains management [98].…”
Section: Type Of Research and Abstractmentioning
confidence: 99%
“…In addition, in a few articles the "Tools, models, framework, methods for decision-making" was combined with other research types. A few examples include with "Business model and management" in an article assessing the costs of municipal waste recycling[96]; with "Economic Model," in an evaluation of the electrical and electronic equipment industry[81]; and with "Policy," in a study developing CE frameworks for the building sector[97] and the Supply Chains management[98].The second most published research type was "Review" (43 articles). Notably, several studies in this category combined with the "Tools, models, framework, methods for decisionmaking" research type, primarily through applying structural modeling techniques such as DEMATEL, AHP, and ELECTRE.Next, for "Process Engineering" (36 articles), a significant focus was observed on biomass or bi-products chemical and biological processes and experimentation with alternative synthetic products.…”
mentioning
confidence: 99%
“…Moreover, it is essential to skilfully use different methods and concepts of management to ensure the continuity of business. "Companies need to design their new business models within the value network in their relations with supply chain members and customers" [3]. Consequently, sustainable business models, in their essence, support companies' effectiveness and contribute to their stable, sustainable functioning in the difficult, ever-changing market.…”
Section: Introductionmentioning
confidence: 99%